IMPLEMENTATION OF VILLAGE FUND (DD) POLICY IN MANAGING MARINE TOURISM POTENTIAL IN BAHOI ECOTOURISM VILLAGE, LIKUPANG BARAT DISTRICT, NORTH MINAHASA REGENCY - Bestrys Arlen Angkouw; Julien Biringan; Steven V. Tarore (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the implementation of the Village Fund (DD) policy in managing marine tourism potential in Bahoi Ecotourism Village, West Likupang District, North Minahasa Regency. Using a qualitative approach with a case study design, data were collected through in-depth interviews with five key informants, field observations, and a study of village financial planning and reporting documents. Data analysis refers to an interactive model of reduction, presentation, and conclusion drawing. The results show that the planning and implementation of DD for the marine tourism sector have met administrative compliance standards through the Village Deliberation mechanism, TPK monitoring, and digital reporting of the Village Finance System (Siskeudes). However, policy implementation is still project-based and oriented towards short-term outputs. Community participation tends to be procedural, not including substantive decision-making regarding asset ownership, retribution schemes, or the distribution of economic benefits. Optimizing implementation is supported by clear regulations, structured vertical coordination, and transparent reporting. Conversely, the program's effectiveness is significantly limited by the village's inadequate fiscal capacity for strategic infrastructure, a deficit in community technical skills, post-village head election political dynamics that disrupt program continuity, and weak horizontal oversight due to a lack of financial literacy and a participatory culture. The study concluded that the implementation of Village Fund Allocation (DD) in Bahoi Village is still at the community-involved tourism stage and has not yet achieved the ideal principles of community-based tourism.